2023
DOI: 10.3389/fmicb.2023.1060337
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms regulating the CRISPR-Cas systems

Abstract: The CRISPR-Cas (Clustered Regularly Interspaced Short Palindromic Repeats- CRISPR associated proteins) is a prokaryotic system that enables sequence specific recognition and cleavage of nucleic acids. This is possible due to cooperation between CRISPR array which contains short fragments of DNA called spacers that are complimentary to the targeted nucleic acid and Cas proteins, which take part in processes of: acquisition of new spacers, processing them into their functional form as well as recognition and cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 168 publications
(188 reference statements)
0
6
0
Order By: Relevance
“…The CRISPR-Cas system provides the host with an adaptive and hereditary immunity against exogenous nucleic acids [36]. In this study, the CRISPR-Cas system arrays (n = 2-10, 74 bp-4468 bp) were identified in all the four V. cholerae genomes (Figure S6).…”
Section: Crispr-cas System Arraysmentioning
confidence: 89%
“…The CRISPR-Cas system provides the host with an adaptive and hereditary immunity against exogenous nucleic acids [36]. In this study, the CRISPR-Cas system arrays (n = 2-10, 74 bp-4468 bp) were identified in all the four V. cholerae genomes (Figure S6).…”
Section: Crispr-cas System Arraysmentioning
confidence: 89%
“…This inhibition is reversible and can be overcome by increasing the concentration of Cas9, suggesting that AcrIIA4 is a competitive inhibitor. , The discovery of ACR proteins has important implications for the use of CRISPR-Cas systems in genome editing and other applications. The presence of ACR proteins can reduce the efficiency and specificity of the CRISPR-Cas system, leading to off-target effects and potentially reducing the therapeutic potential of this technology. , …”
Section: Bacterial Mechanisms Of Resistancementioning
confidence: 99%
“…The presence of ACR proteins can reduce the efficiency and specificity of the CRISPR-Cas system, leading to off-target effects and potentially reducing the therapeutic potential of this technology. 189,195 Anti-anti-CRISPR strategies refer to the development of tools and techniques to overcome the inhibitory effects of anti-CRISPR (ACR) proteins on CRISPR-Cas systems. These strategies are important for improving the efficiency and specificity of CRISPR-Cas systems in genome editing and other applications.…”
Section: ■ Bacterial Mechanisms Of Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, researchers are constantly improving the performance of the CRISPR/Cas system, taking advantage of its high target sequence specificity and programmability to meet the requirements of specificity, sensitivity, speed, cost and simplicity in molecular diagnostic processes. In previous reviews, there have been discussions on the regulatory mechanisms, classification, [7] biological editing in food and agriculture, [8] non nucleic acid testing, [9] and nucleic acid testing [10] of the CRISPR‐Cas system.…”
Section: Introductionmentioning
confidence: 99%